If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3x + 12 = 11 Reorder the terms: 8 + 12 + -3x = 11 Combine like terms: 8 + 12 = 20 20 + -3x = 11 Solving 20 + -3x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -3x = 11 + -20 Combine like terms: 20 + -20 = 0 0 + -3x = 11 + -20 -3x = 11 + -20 Combine like terms: 11 + -20 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 0.3x-0.7x-27=1 | | 6x+10038=x-28483 | | 15-2x=41 | | -7(x-4)+8x=26 | | 2(r)-7=r+15 | | 11w-13w=4 | | 41-3n=2 | | 6x+9=15x | | n^2-3n-40= | | 9x-14=6x-13 | | -5n+3n=4n-5n | | x^2=x+25 | | y=17x+544 | | 7x+10=27 | | 6w+5-5w=8-3 | | 6=2x+6(x+5) | | -112=7j | | -4(x+2)=6x+10x+2 | | (x+5)2-(x+5)(x-5)= | | -5r-2r=-15-8r+3+7 | | 4x-5=4x+9 | | -3w+8(w-4)=-2 | | 7-2b=19 | | 75=10x-5 | | 1+b=-18-4 | | 27+3x=111 | | -13m+7m=19-73 | | 5x+11=12x-10 | | 10x-2-6x=3y-2+y | | 3x+15+9x+21=180 | | -11x-20=10+40 | | 6y+12=3t+14 |